Microplastic Pollution in the Aquatic Ecosystem of Gili Trawangan, Lombok: Abundance, Characteristics, and Implications in Tourism Area - Nadda Khalila Chairunnisa; Moh. Awaludin Adam; Dining Aidil Candri (Postgraduate, University of Mataram, 2025)
Microplastics (MPs) have become an interesting topic of discussion especially after many studies reported their presence in aquatic ecosystems. Pollution by microplastic particles in aquatic systems is a critical issue the world that has the potential to damage aquatic ecosystems. Therefore, this study aims to identify the abundance and characteristics of MPs in water, sediment and seagrass in tourist areas. Samples were obtained from three location categories, first the port, second the hotel area and third the residential area located in the Gili Trawangan tourist area, Lombok, Indonesia. After optimization of extraction, characterization was carried out using a stereo microscope to identify MPs. The results show that the average abundance of MPs in the three location categories is, 13.25 ± 17.21; 19.25 ± 23.30; and 16.50 ± 18.52 particles/L at water, 22.00 ± 30.84; 20.00 ± 30.80; and 6.00 ± 8.49 particles/kg dry weight (dry weight) sediment, and 17.50 ± 15.69; 16.25 ± 22.56; and 8.25 ± 8.46 particles/individual at seaweed. Then from this abundance, the types of MPs were found in the form of fragments, fibers, films and pellets, where the dominant colors are black, yellow, blue, red and green, with the highest size < 500 µm. From this study it is necessary to see the impact of MPs on seaweed and the aquatic environment around Gili Trawangan.